Career Adaptability and Resilience as Predictors of Subjective Well-Being: Testing Self-Efficacy as a Mediator in University Students - Sinta Amanda Putri; Helma Malini; Mazayatul Mufrihah; Rizani Ramadhan (Journal of Educational Management Research, 2026)
From a Human Resource Management perspective, final-year students are considered prospective workforce members as they are in a transition phase from education to the labor market and are preparing competencies and psychological readiness required by organizations. This study aims to analyze the effects of career adaptability and resilience on subjective well-being, with self-efficacy serving as a mediating variable. This study employed a quantitative approach using a survey method by distributing questionnaires to 240 final-year students undergoing career transition. The collected data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results revealed that career adaptability and resilience had positive and significant effects on subjective well-being. Furthermore, self-efficacy was found to significantly mediate the relationships between career adaptability and resilience and subjective well-being. These findings imply that strengthening adaptability, resilience, and self-efficacy can support students’ psychological well-being and contribute to preparing a more adaptive, resilient, and work-ready future workforce.